Metabolomic analysis of synovial fluid from healthy and pathological equine joints and tendon sheaths using high-resolution 1H Nuclear Magnetic Resonance - Guadalupi, Marta; Girelli, Chiara Roberta; Della Tommasa, Simone; Corte, Federica Della; Crovace, Alberto Maria; Fanizzi, Francesco Paolo; Brehm, Walter; Lacitignola, Luca (Frontiers in Veterinary Science, 2025)
IntroductionJoint and tendon sheath diseases are a major cause of lameness and reduced performance in horses. Synovial fluid composition changes in response to pathological processes and metabolomic profiling offers a promising approach to detect these alterations. While equine joint metabolomics has been explored, little is known about the metabolomic profile of tendon sheaths. This study aimed to characterize and compare the synovial fluid metabolomic profiles of healthy and pathological joints and tendon sheaths in horses using high-resolution 1H Nuclear Magnetic Resonance spectroscopy, and to identify potential biomarkers associated with musculoskeletal pathology.MethodsSynovial fluid samples were collected from healthy joints and tendon sheaths of routinely slaughtered animals, and from pathological joints and tendon sheaths from owned athletic horses affected by inflammatory or degenerative conditions. The samples were analyzed using 1H Nuclear Magnetic Resonance spectroscopy. Synovial fluid samples were collected from healthy joints and tendon sheaths of routinely slaughtered animals, and from pathological joints and tendon sheaths from owned athletic horses affected by inflammatory or degenerative conditions. The samples were analyzed using 1H Nuclear Magnetic Resonance spectroscopy.ResultsThe metabolomic analysis of equine synovial fluid identified amino acids, organic acids, glucose isomers, and other metabolites. No significant differences were observed in the metabolic profiles of synovial fluid from healthy joints and tendon sheaths (PCA: R2X = 0.761, Q2 = 0.372; OPLS-DA: R2X = 0.48; R2Y = 0.292; Q2 = −0.143). In contrast, a clear separation with distinct clustering was observed between healthy and pathological synovial fluid joints and tendon sheaths (PCA: R2X = 0.88, Q2 = 0.684; OPLS-DA: R2X = 0.775; R2Y = 0.6772, Q2 = −0.432). Multivariate statistical analysis revealed distinct clustering of healthy joints samples grouping closely with pathological joints samples (OPLS-DA: R2X = 0.662; R2X = 0.859, Q2 = 0.786). These findings were supported by univariate analysis (t-test, p < 0.05). Similarly, multivariate statistical analysis showed strong discrimination between healthy and pathological tendon sheaths synovial fluid (OPLS-DA: R2X = 0.742; R2Y = 0.892, Q2 = 0.842), also supported by univariate analysis (t-test, p < 0.05).DiscussionMetabolomic profiling by 1H-NMR effectively distinguished healthy from pathological synovial fluid in joints and tendon sheaths, providing a clear metabolic fingerprint of disease-related alterations that may support earlier detection and a better understanding of equine musculoskeletal disorders. The main limitation of this study was the small sample size, particularly for tendon sheath samples. Additional synovial fluid specimens from both healthy and pathological joints and tendon sheaths would be needed to implement metabolomic data. High-resolution 1H Nuclear Magnetic Resonance spectroscopy proves to be a valuable tool for differentiating healthy from pathological equine synovial fluid. Metabolomic analysis revealed a specific metabolic fingerprint in diseased joints and tendon sheaths, supporting its potential role in the diagnosis and monitoring of orthopedic conditions in horses.